Construction Management Applications: Challenges in Developing Execution Control Plans - Onder, Nilufer; Mukherjee, Amlan; Tang, Pei (Proceedings of the International Conference on Automated Planning and Scheduling, 2010)
The objective of automated planners is to synthesize sequences of actions (called policies in MDP frameworks) that will achieve a predetermined goal given a fully or partially observable formal representation of the domain. In contrast, the main characteristic of project management is the greater emphasis on plan execution under uncertainty as opposed to plan synthesis. This paper explains the need to transition from automated plan synthesis to plan management and identifies the challenges for the planning and scheduling communities using examples of construction projects.